Finding the plot : a maternal approach to madness in literature - Rogers, Megan (Demeter Press, 2017)
Over the past fifty years, feminist literary criticism has become theoretical rather than practical, severing any relationship between literary analysis and the real lived experiences of women. An example of this disconnect is the way in which the madwoman in feminist literature has become a lauded icon of liberation, when in reality her situation would be seen as anything but empowered. Finding the Plot takes this example to task, arguing that in fact any interpretation of women's madness as subversive reinforces the very gender stereotypes that feminist literary criticism should be calling into question.